Dirāsatu al Naghamāti fī Qirā’ati al Syi’ri li Kitābi “Majmū’ati Maulidi Wādi’iyyati” al Barzanji Naẓami ‘inda al Mujtama’i Malāyu Jāmbi (Dirāsatun fī ‘ilmi al Adabi) - Anggraini, Susi; Sudiarti, Sri (Al-Uslub: Journal of Arabic Linguistic and Literature, 2020)
The text of Maulid Al-Barzanji nazom can be considered a work of religious Arabic literature or literature that is so old and still acceptable to the wider community from time to time، even becoming popular in the life of the malay community jambi.. In this thesis discussion، the author discusses the singing of the song berzanji nazom in the book majmu'ah maulid wad'yyah in jambi malay community، especially in the estuary jambi in the village of sekernan and setiris. The purpose of this research is to know what is the most popular song among the jambi malay community، and to know what causes the song is popular among the jambi malay community، and to know the development of the song among jambi malay community. The type of research used is field research. Can be concluded from the results of this study :1) jambi malay people when singing the poem berzanjii nazom that is in the book majmu'ah maulid wad'iiyah''they chant it with the song rost، and nahwand.karna this second song contains characters، Rost song is dynamic and passionate.and so does nahwan song also contains spirit character and very firm and nuanced ksedihan.2)and among the malay community jambi they are very happy with the art. and they can wave it with various kinds of cloves or variations so that the listeners can live the poem، with variations and cloves of beautiful cloves and nuances of sadness so that the listener can live the poem then that is thus the cause of the masyurnya song. and when there is an alimatur arsyi event and circumcision of the poem is also chanted with such a song and there is also a competition in the MTQ event.